Peningkatan Kinerja Guru Melalui Supervisi Edukatif Kolaboratif Secara Periodik Di SD Negeri 01 Kepahiang - Ariani, Farida (JPT : Jurnal Pendidikan Tematik, 2021)
This study aims to describe the steps of collaborative educational supervision periodically in implementing learning, assessing learning achievement, carrying out follow-up assessments of student achievement and preparing lesson plans. So that learning objectives can be achieved. The research method used is descriptive qualitative method. This research includes research on school actions for initial data collection, data analysis results at the end of each cycle, as well as other responses from teachers on the implementation of collaborative educational supervision. The results of the study indicate that supervision of all teachers needs to be carried out periodically and set at the beginning of the school year (during the division of tasks). Educational supervision turns out to lead to an increase in teacher performance and student learning outcomes if it is carried out collaboratively. Collaborative educational supervision will be meaningful if the supervisor is a colleague who is already capable of the subject in question. Principals need to provide opportunities for teachers who are considered capable of supervising other teachers